An important, but neglected aspect of learning assistance in higher education: Exploring the digital learning capacity of academic language and learning practitioners - Podorova, Anna; Irvine, Sarah; Kilmister, Michael; Hewison, Richard; Janssen, Amanda; Speziali, Alejandra; Balavijendran, Logan; Kek, Megan; McAlinden, Maggie (Journal of University Teaching and Learning Practice, 2019)
Digital literacy has become increasingly significant in tertiary environments, as institutions move towards preparing students for 21st century workplaces and careers that emphasise digital literacy. As such, Academic Language and Learning (ALL) practitioners within these institutions are under pressure to possess familiarity and skills in the digital education space. Despite this need, there is a shortage of evidence that identifies the competencies or gaps in the current knowledge that ALL advisors have in Australian tertiary institutions; there is also a lack of awareness about how to address the gaps in knowledge for technology-enhanced learning and academic support. In light of this lacuna, in late 2018, the Association for Academic Learning and Language (AALL), the professional body for Academic Language and Learning practitioners, established a working group to investigate the knowledge and gaps in digital literacy in the ALL profession. The authors of this paper are all members of this working group and aim to explore the state of digital learning in their field. The long-term aim of the working party is to develop research-led resources and strategies to assist in the professionalisation and upskilling of ALL staff in technology-enhanced academic language development and support. This paper reports on the preliminary findings of a mixed-method participatory action research study of ALL practitioners’ preferences, competencies and confidence in the digital learning space. It is hoped that this study will provide members within the AALL professional body, as well as tertiary educators generally, with strategies required to identify, develop and maintain effective digital literacies across the higher education sector.